In vivo evaluation of honey as a new medicament for vital pulp therapy in primary teeth - K Krishna Kumari; E Sridevi; A Jogendra Sai Sankar; A Satya Gopal; K Pranitha; M G Manoj Kumar (Wolters Kluwer Medknow Publications, 2017)
Objectives: In spite of clinical success, the pulpotomy technique has been questioned for safety and effectiveness of currently available medicaments. In search of newer materials, there is a rapid research toward natural health remedies. Thus, an in vivo study was conducted to evaluate and compare the clinical and radiographic success of honey and formocresol (FC) as pulpotomy agents. Materials and Methods: A total of 100 mandibular primary molars were selected from 50 healthy children aged between 3 and 8 years following the inclusion and exclusion criteria for pulpotomy procedure. The teeth were divided into two equal groups; in Group A, honey was used as pulpal medicament and in Group B, FC as control. Further, all the pulpotomised teeth were restored with stainless steel crowns and postoperative evaluation was done at 1, 3, 6, 9, and 12 months interval. Results: Clinically, both the groups showed 100% success during the follow-up periods. Even though 100% radiographic success was recorded for Group A and B after 1 month interval, the values dipped to 95.6% and 95.4% at 3 months, 91.3% and 90.9% after 6 months, 91.3% and 86.3% after 9 months, and 86.9% and 77.2% after 12 months, respectively. Conclusion: Although honey showed promising results both clinically and radiographically, long-term follow-up is recommended to investigate the efficacy of honey as viable alternative to FC.